Characteristics and critical success factors for implementing problem-based learning in a human resource-constrained country - Karen R.N. Giva; Sinegugu E. Duma (AOSIS, 2015)
Background: Problem-based learning (PBL) was introduced in Malawi in 2002 in order to improve the nursing education system and respond to the acute nursing human resources shortage. However, its implementation has been very slow throughout the country. Objectives: The objectives of the study were to explore and describe the goals that were identified by the college to facilitate the implementation of PBL, the resources of the organisation that facilitated the implementation of PBL, the factors related to sources of students that facilitated the implementation of PBL, and the influence of the external system of the organisation on facilitating the implementation of PBL, and to identify critical success factors that could guide the implementation of PBL in nursing education in Malawi. Method: This is an ethnographic, exploratory and descriptive qualitative case study. Purposive sampling was employed to select the nursing college, participants and documents for review.Three data collection methods, including semi-structured interviews, participant observation and document reviews, were used to collect data. The four steps of thematic analysis wereused to analyse data from all three sources. Results: Four themes and related subthemes emerged from the triangulated data sources. The first three themes and their subthemes are related to the characteristics related to successful implementation of PBL in a human resource-constrained nursing college, whilst the last themeis related to critical success factors that contribute to successful implementation of PBL in ahuman resource-constrained country like Malawi. Conclusion: This article shows that implementation of PBL is possible in a human resource-constrained country if there is political commitment and support.